Utility of reticulocyte hemoglobin in diagnosing latent iron deficiency and iron deficiency anemia - Chandrashekar, Kavya; T., Yashoda H.; Reddy, Varsha Monica (International Journal of Contemporary Pediatrics, 2020)
Background: Iron deficiency is the most common cause of anemia and studies have shown poor cognition, psychomotor and social/emotional development in children who are deficient in iron, even with normal hemoglobin levels, the so-called Latent phase of Iron deficiency. It is therefore crucial to identify LID, as well as IDA at the earliest stage, in order to initiate treatment. Many tests like serum ferritin and soluble transferring receptor(sTfR) have been described collectively as a panel to detect iron deficiency; however no single test is specific enough to be used independently. Also during treatment it takes weeks to observe changes in Hb, hematocrit or RBC indices, hence the need for a more sensitive and reliable test. Objective was to evaluate effectiveness of CHr in diagnosing LID and IDA. Methods: Samples were collected from 180 children, clinically suspected to be anemic. Complete hemogram and Iron profile were measured. Three groups were defined, LID (Tfsat <20%, Hb >11g/dL; n=52), IDA (Tfsat <20%, Hb <11g/dL; (n=84) and controls (Tfsat >20%, Hb >11g/dL; n=44). The mean values of RBC indices, Iron profile and CHr was compared across the groups. A cut off value of <26 pg CHr was taken to represent Iron deficiency state. Results: Comparison between anemic group and control found that all RBC indices were found to be significantly lower including Reticulocyte hemoglobin. All of the variables in anemic group were lower compared to latent iron deficient group except MCHC and reticulocyte count. CHr was found to be statistically lower in LID and IDA group in comparison to control group. Conclusions: CHr can be used as a valuable indicator in diagnosis as well as follow-up of LID and IDA, which is easily available and inexpensive.